Identifying the categories of spiritual experience encountered by therapists in their clinical work - Ross, J (Taylor and Francis, 2016)
Spirituality has replaced religion in popular culture and its presence is being felt in the therapeutic world. Using a questionnaire completed by 104 people utilizing 6 descriptive definitions of spirituality and 36 categories of spiritual experience, three meta-themes of forms of spirituality emerged through a thematic analysis. These are spiritualties of the Sacred, the Self and the Senses. When the therapist’s theoretical orientation is identified there are different expressions of the spirituality that emerges. Of specific importance is that due to approximately 90% of the respondents being female what emerges therefore is an expression of female spirituality. More research will be required to identify if there is matching male spirituality.